Nerium indicum leaf alleviates iron-induced oxidative stress and hepatic injury in mice. (July 2015) - Ghate, Nikhil Baban; Chaudhuri, Dipankar; Panja, Sourav; Mandal, Nripendranath
Abstract Context: Nerium indicum Mill. (Apocynaceae) was reported for its efficient in vitro antioxidant and iron-chelating properties. Objective: This study demonstrates the effect of 70% methanol extract of N. indicum leaf (NIME) towards in vitro DNA protection and ameliorating iron-overload-induced liver damage in mice. Materials and methods: Phytochemical and HPLC analyses were carried out to standardize the extract and the effect of Fe2+-mediated pUC18 DNA cessation was studied. Thirty-six Swiss Albino mice were divided into six groups of blank, negative control (iron overload only), and iron-overloaded mice receiving 50, 100, and 200 mg/kg b.w. doses of NIME and desirox (20 mg/kg b.w.). The biochemical markers of hepatic damage, various liver and serum parameters, and reductive release of ferritin iron were studied. Results and discussion: The presence of different phytocomponents was revealed from phytochemical and HPLC analyses. A substantial supercoiled DNA protection, with [P]50 of 70.33 ± 0.32 µg, was observed. NIME (200 mg/kg b.w.) significantly normalized the levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and bilirubin by 126.27, 125.25, 188.48, and 45.47%, respectively. NIME (200 mg/kg b.w.) was shown to alleviate the reduced levels of superoxide dismutase, catalase, glutathione-S-transferase, and non-enzymatic-reduced glutathione, by 48.95, 35.9, 35.42, and 13.22%, respectively. NIME also lowered raised levels of lipid peroxidation, protein carbonyl, hydroxyproline, and liver iron by 32.28, 64.58, 136.81, and 83.55%, respectively. Conclusion: These findings suggest that the active substances present in NIME may be capable of lessening iron overload-induced toxicity, and possibly be a useful drug for iron-overloaded diseases.